Protein Acetylation/Deacetylation: A Potential Strategy for Fungal Infection Control - Chen, Junzhu; Liu, Qiong; Zeng, Lingbing; Huang, Xiaotian (Frontiers in Microbiology, 2020)
Protein acetylation is a universal post-translational modification that fine-tunes the major cellular processes of many life forms. Although the mechanisms regulating protein acetylation have not been fully elucidated, this modification is finely tuned by both enzymatic and non-enzymatic mechanisms. Protein deacetylation is the reverse process of acetylation and is mediated by deacetylases. Together, protein acetylation and deacetylation constitute a reversible regulatory protein acetylation network. The recent application of mass spectrometry‐based proteomics has led to accumulating evidence indicating that reversible protein acetylation may be related to fungal virulence because a substantial amount of virulence factors are acetylated. Additionally, the relationship between protein acetylation/deacetylation and fungal drug resistance has also been proven and the potential of deacetylase inhibitors as an anti-infective treatment has attracted attention. This review aimed to summarize the research progress in understanding fungal protein acetylation/deacetylation and discuss the mechanism of its mediation in fungal virulence, providing novel targets for the treatment of fungal infection.